Western higher education in Asia and the Middle East politics, economics, and pedagogy - Gray, Kevin (Kevin W.); Bashir, Hassan 1971-; Keck, Stephen (Lexington Books, 2017)
This multidisciplinary volume highlights the transformed nature of the relationship between higher education and society in the 21st century. In particular, it argues that the development of the global university, especially in the non-western world, has transformed the traditional understanding of the relationship between higher education and society. This has important implications for the relations of state, as education has not only become an object of national development policy but for many states an important export. The history of the university reflects the decisive social transformations which have given definition and identity to both new nations and modern societies. In the post-war period, universities in the industrialized world underwent a radical shift